2022
DOI: 10.1038/s41385-022-00546-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 regulates goblet cell numbers through Notch signaling in the developing zebrafish intestine

Abstract: Cytokines are immunomodulatory proteins that orchestrate cellular networks in health and disease. Among these, interleukin (IL)-10 is critical for the establishment of intestinal homeostasis, as mutations in components of the IL-10 signaling pathway result in spontaneous colitis. Whether IL-10 plays other than immunomodulatory roles in the intestines is poorly understood. Here, we report that il10, il10ra, and il10rb are expressed in the zebrafish developing intestine as early as 3 days post fertilization. CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…IL-10 prevents protein misfolding via STAT1 and STAT3 signal transduction pathways, and thereby maintains mucin production in goblet cells and integrity of the mucus barrier (Figure 2). 102,103 IL-10sensitized mice display increased mucin production in airway epithelium after infection with RSV. 104,105 Lee et al 106 demonstrated that IL-10 can induce goblet cell proliferation and enhance mucin gene expression to induce airway diseases in transgenic mice with overexpression of IL-10 in the lungs.…”
Section: Il-10 and Mucinmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-10 prevents protein misfolding via STAT1 and STAT3 signal transduction pathways, and thereby maintains mucin production in goblet cells and integrity of the mucus barrier (Figure 2). 102,103 IL-10sensitized mice display increased mucin production in airway epithelium after infection with RSV. 104,105 Lee et al 106 demonstrated that IL-10 can induce goblet cell proliferation and enhance mucin gene expression to induce airway diseases in transgenic mice with overexpression of IL-10 in the lungs.…”
Section: Il-10 and Mucinmentioning
confidence: 99%
“…(8) IL‐10 induces Muc2 gene expression through activation of JAK2/STAT1/STAT3 signaling pathway. 102 , 103 IL‐10 can indirectly induce MUC5AC secretion by enhancing the inflammatory process of IL‐13. 106 …”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish Notch signaling was described to be involved in larval zebrafish heart regeneration [81] and in the establishment of arterial system development and arterialvenous identity [88]. The Notch pathway controls cell fate decisions during embryonic development [89,90]; activation of Notch is required for initiating endothelial cell and Hemogenic Endothelium formation in the dorsal aorta [91] and for regulating goblet cell numbers in the developing zebrafish intestine [92].…”
Section: Notchmentioning
confidence: 99%
“…Edwardsiella tarda, a common pathogen that can cause edwardsiellosis, is a Gram-negative bacterium that can affect a wide range of hosts, including aquatic animals, amphibians, reptiles, and mammals [24][25][26]. The IL-10 family members are essential for maintaining creaturely homeostasis and provide effective protection against microbial infection [27][28][29][30]. However, studies on these immune-related genes of spotted sea bass are not enough.…”
Section: Introductionmentioning
confidence: 99%